The Circus Is in Town : Sport, Celebrity, and Spectacle - Rosen, Joel Nathan, 1961-; Alexander, Lisa Doris (Book collections on Project MUSE., 2022)
"In this book on sport and the nature of reputation, editors Lisa Doris Alexander and Joel Nathan Rosen have tasked their contributors with examining reputation from the perspective of celebrity and spectacle, which in some cases can be better defined as scandal. The subjects chronicled in this volume have all proven themselves to exist somewhere on the spectacular spectrum-the spotlight seemed always to gravitate toward them. All have displayed phenomenal feats of athletic prowess and artistry, and all have faced a controversy or been thrust into a situation that grows from age-old notions of the spectacle. Some handled the hoopla like the champions they are, or were, while others struggled and even faded amid the hustle and flow of their runaway celebrity. While their individual narratives are engrossing, these stories collectively paint a portrait of sport and spectacle that offers context and clarity. Written by a range of scholarly contributors from multiple disciplines, The Circus Is in Town: Sport, Celebrity, and Spectacle contains careful analysis of such megastars as LeBron James, Tonya Harding, David Beckham, Shaquille O'Neal, Maria Sharapova, and Colin Kaepernick. This final volume of a project that has spanned the first three decades of the twenty-first century looks to sharpen questions regarding how it is that reputations of celebrity athletes are forged, maintained, transformed, repurposed, destroyed, and at times rehabilitated. The subjects in this collection have been driven by this notion of the spectacle in ways that offer interesting and entertaining inquiry into the arc of athletic reputations"--